Microbial Profiling of Potato-Associated Rhizosphere Bacteria under Bacteriophage Therapy - Samar Mousa; Mahmoud Magdy; Dongyan Xiong; Raphael Nyaruabaa; Samah Mohamed Rizk; Junping Yu; Hongping Wei (MDPI AG, 2022)
Potato soft rot and wilt are economically problematic diseases due to the lack of effective bactericides. Bacteriophages have been studied as a novel and environment-friendly alternative to control plant diseases. However, few experiments have been conducted to study the changes in plants and soil microbiomes after bacteriophage therapy. In this study, rhizosphere microbiomes were examined after potatoes were separately infected with three bacteria (Ralstonia solanacearum, Pectobacterium carotovorum, Pectobacterium atrosepticum) and subsequently treated with a single phage or a phage cocktail consisting of three phages each. Results showed that using the phage cocktails had better efficacy in reducing the disease incidence and disease symptoms' levels when compared to the application of a single phage under greenhouse conditions. At the same time, the rhizosphere microbiota in the soil was affected by the changes in micro-organisms' richness and counts. In conclusion, the explicit phage mixers have the potential to control plant pathogenic bacteria and cause changes in the rhizosphere bacteria, but not affect the beneficial rhizosphere microbes.